Modern Diagnostic Methods for Identifying Allergic Diseases - To’xtaboyevna, Matniyozova Zaynab (Journal of Science in Medicine and Life, 2024)
The allergen-specific diagnosis during allergic diseases aims at establishing the causal significance of allergens in the occurrence of allergic disease, which bears high importance for the development of efficient therapeutic and prophylactic programs for children suffering from allergic diseases. During the last years the opportunities of diagnosis of allergic diseases have broadened thanks to standardization of the majority of inhalation allergens. Specific diagnosis is based on the evaluation of allergic history data, results of allergy skin tests, use of in vitro allergy diagnosis tests and the performance of provocation tests [1].